The presence of only one of five exoribonucleases is sufficient to support the growth of Escherichia coli. - Kelly, K O (1992)
Escherichia coli contains multiple exoribonucleases. Strains lacking the exoribonucleases RNase II, D, BN, T, and PH are inviable. The introduction of a chromosomal, wild-type copy of the gene for any one of these enzymes is sufficient to allow cell growth, with the enzymes being in the following order of effectiveness: RNase T > RNase PH > RNase D > RNase II > RNase BN. The data indicate that these five exoribonucleases functionally overlap in vivo and that any one of them can take over the functions of all the others, although with various efficiencies.